Assessment of adsorption capacity on pallet coal - Freitas, Jhonatan Junio de; Ströher, Gylles Ricardo; Ströher, Gisely Luzia (Seven Editora, 2024)
Pallets are widely used for moving cargo, however, they are often disposed of inappropriately, due to the cost associated with their correct disposal. This study focused on transforming expired pallets into pallet coal (PC) and investigating its properties, carrying out the determination of the Langmuir isotherm, employing primary standard solutions. The results obtained with the gravimetric yield were 66.05%, which indicates an excellent cost/benefit. The isotherm obtained is characteristic of a favorable adsorption, with saturation of the sites occurring at around 0.014 g.L-1, with a layer close to a concentration of 3.3 mol.L-1. The active area of this pallet coal was estimated at 715.94m2.g-1. This study was dedicated to evaluating the adsorption capabilities of discarded material, aiming for its reuse in a more sustainable way, thus contributing to the preservation of the environment. Transforming discarded material into an adsorbent not only adds value to the product, but also significantly reduces industry costs associated with conventional disposal. DOI:https://doi.org/10.56238/sevened2024.007-016